New Pharmacotherapeutic Posssibilities in Contemporary Dentistry - R. Slezák; Z. Janovská; I. Lindrová; V. Radochová (Czech Dental Chamber, 2015)
Background: Both new active substances and medical devices are used in dentistry. Especially some diseases of the mucous membrane of the mouth, lip vermillion, salivary glands, and bone of jaws are the major focus on drug development. An acyclic nucleoside antiviral analogue Zovirax Duo containing aciclovir and cortisol is the cream peparation for topical treatment of labial herpes with additional antiinflammatory effect. Filmogel® URGO Afty gel was designed for topical therapy of recurrent aphthous ulcers. Emofix gel was designed for local therapy of mucosal bleeding of various origin. Betaine, xylitol and olive oil containing products (Xerostom) have been declared for both substitutional and stimulating therapy of hyposialia of various origin. There are initial reports about the use of bone anabolic drug teriparatide, recombinant agent used for the therapy of severe skeletal defects in osteoporosis, in dental surgery. Biologic agents belimumab, abatacept, and epratuzumab are clinically tested in active forms of primary Sjőgren's syndrome. Live atenuated vaccine targeted against varicella-zoster virus in older individuals serves in the prophylaxis of the herpes zoster. Conclusion: Potential benefit of the above mentioned substances and devices might be seen in dental medicine disciplines.